Impact of Non Tariff Measure on Indonesian Cacao Exports - Andi Tenri Darhyati; Suharno Suharno; Amzul Rifin (Hasanuddin University, 2017)
Increased awareness of food safety issues has resulted in non-tariff measure in the form of sanitary and phytosanitary, technical barrier to trade applied to various importing countries. The policy is widely applied by various countries on agricultural commodities, especially Cocoa. Cocoa is Indonesia's flagship commodity exported to many countries. The purpose of this research is to analyze the implementation and impact of non tariff measure on Indonesian cocoa exports. The model used in this research is to estimate the result of inventory approach in gravity model. The results show that Sanitary and Phytosanitary policy has an effect on decreasing export value of Indonesian Cocoa while Technical Barrier to Trade has no significant effect. SPS policy is mostly applied to Cocoa Beans while TBT is more applied to processed cocoa. So, Indonesia needs to improve the processing of cocoa beans such as cacao shells, cacao paste, cacao butter, cacao powder, chocolate and other preparations. The government needs to provide socialization to Indonesian cocoa agribusiness entrepreneurs in the implementation of sanitary and phytosanitary policy. Government programs or policies are designed according to the characteristics of SPS and TBT.